Formulation and evaluation of patchouli oil gel for burn wound - Febriyenti Febriyenti; Rizki Febrika Putri; Netty Suharti (Fakultas Farmasi Universitas Andalas, 2019)
Essential oils of the patchouli leaves (Pogostemon cablin, Benth) was known has the antibacterial effect and could be used to treat the burn. Aim of this study is to formulate patchouli oil into gel dosage form. Patchouli oil was used at three concentrations i.e. 2% (F1), 4% (F2) and 6% (F3). Evaluation of the resulting formulas includes examining its general appearance, homogeneity, skin irritation test, pH and spreadability test. Based on the evaluation data, it was found that gel with 2% patchouli oil was transparent. The greater the concentration of patchouli oil, the more opaque the gel is produced. The other parameters give results that are not different for the three formulas.